2019
DOI: 10.1088/1361-6560/ab5323
|View full text |Cite
|
Sign up to set email alerts
|

Temperature control in TTFields therapy of GBM: impact on the duty cycle and tissue temperature

Abstract: In TTFields therapy, Optune® is used to deliver the electric field to the tumor via 4 transducer arrays. This device monitors the temperature of the transducers and reduces the current whenever a transducer reaches 41 °C. Our aim is to quantify Optune’s duty cycle and to predict the steady-state temperature distribution in the head during GBM treatment. We used a realistic head model and the finite element method to solve Pennes equation and to simulate how Optune operates considering that current reduces to z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…It is worth noting that there was an observed heating of the phantom during the water phantom measurements that appear to be consistent with Joule heating. In a clinical study, 10% to 17% of patients felt a heat sensation, 27 indicating that hyperthermia could potentially be another synergistic effect of the simultaneous therapies, [27][28][29][30] although this was superficial heating and presumed not to be heating of the deep tissue. This phenomenon is being studied in greater detail in our upcoming work, which will also account for inherent temperature regulation within a patient.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that there was an observed heating of the phantom during the water phantom measurements that appear to be consistent with Joule heating. In a clinical study, 10% to 17% of patients felt a heat sensation, 27 indicating that hyperthermia could potentially be another synergistic effect of the simultaneous therapies, [27][28][29][30] although this was superficial heating and presumed not to be heating of the deep tissue. This phenomenon is being studied in greater detail in our upcoming work, which will also account for inherent temperature regulation within a patient.…”
Section: Discussionmentioning
confidence: 99%
“…The values assigned to each tissue and material were chosen after an extensive literature review. Additional details about these values and how the studies were performed can be found in [31].…”
Section: Simulations' Conditionsmentioning
confidence: 99%
“…In our first work [31], we predicted the thermal impact of TTFields and quantified the duty cycle of Optune. We defined the latter as the time that each configuration is on divided by the maximum time it could be delivering the fields and assumed that there was a complete current shutdown whenever the average temperature of any transducer reached a cutoff temperature.…”
Section: Duty Cycle and Effective Electric Field At The Tumormentioning
confidence: 99%
See 1 more Smart Citation
“…The temperature variations that occur during TTFields therapy were first investigated by Gentilal et al ( 2019 ) through in-silico studies. In that work, it was seen that, in each tissue, the temperature increased mainly underneath the regions where the arrays were placed, and they were very superficial.…”
Section: Introductionmentioning
confidence: 99%